A Dictionary of Chemistry - Oxford University Press (Oxford Oxford University Press, 2016)
Fully revised and updated, the seventh edition of this dictionary covers all aspects of chemistry, including physical and biochemistry, in over 5000 concise and accessible entries. It is the ideal reference resource for students of chemistry, either at school or university
Include Appendix
Keywords: Chemistry